THE LAW ON MARRIAGE OF GIRLS OUT OF WEDLOCK BY THEIR BIOLOGICAL FATHERS FROM THE PERSPECTIVE OF IMAM SYAFI'I AND IMAM HANAFI - Alfaatih, Muhammad Akhmal; Mukri, Syarifah Gustiawati; Yono, Yono (IBN KHALDUN BOGOR, 2024)
The aim of this research is to analyze the opinions of the Hanafi school and the Shafi'i school regarding the law of marrying children resulting from adultery with their biological father. Apart from that, to find out the reasons for the law regarding the marriage of a child resulting from adultery with her biological father. The results of the research show that according to the view of the Hanafi school, children born out of wedlock or outside a valid marriage are makhluqoh (children created) from the semen of their biological father, and it is forbidden for their father to marry his adulterous child. Meanwhile, according to the Shafi'ischool of thought, adulterous children or children born outside of a legal marriage are ajnabiyyah (foreigners) who are completely alienated and have no rights to their biological father, and it is permissible for the biological father to marry his adulterous child if she is a girl. The Hanafi School interprets it to mean linguistically or essentially or also called in general, which means sexual intercourse in a broad sense without any distinction between halal sexual intercourse and haram sexual intercourse. Meanwhile, the Syafi'i school of thought interprets the word an-nikah in Surah an-Nisa' verse 22 only as a marriage bond that is valid according to the Shari'a. Then from the word banatukum in surah an-Nisa' verse 23, the Hanafi school believes that the word Banatukum in surah An-Nisa': 23 already includes children of adultery because children of adultery are also